Implementasi Nilai-Nilai Karakter dalam Kegiatan Pembelajaran Pendidikan Pancasila Kelas V di SDN 6 Ampenan - Imas Herawati; Khairun Nisa; Hikmah Ramdhani Putri (Mataram University, 2026)
Character values are a set of attitudes, behaviors, and morals that guide individuals in acting and interacting in everyday life. Instilling character values from an early age is very important because it plays a role in shaping the personality of students so that they become individuals with noble character, are responsible, able to cooperate, and have the ability to think critically in facing various life problems. This study aims to analyze the implementation of character values in Pancasila Education learning at State Elementary School 6 Ampenan. This study uses a descriptive qualitative approach with research subjects of educators and fifth grade students. Data collection techniques were carried out through observation, interviews, documentation, and questionnaires. Data analysis uses the Miles and Huberman model which includes data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that there are character values implemented in Pancasila Education learning, namely faith and piety, global diversity, mutual cooperation, independence, and critical reasoning. The values of faith and piety are reflected through prayer activities before learning and polite attitudes. The value of global diversity is seen from the attitude of respecting differences and tolerance. The value of mutual cooperation is evident in students' cooperation during group discussions. The value of independence is reflected in their responsibility in completing assignments and self-confidence. Meanwhile, the value of critical reasoning is evident in students' ability to ask and answer questions during the learning process.